Post-radiation levator ani atrophy is associated with worse Low Anterior Resection Syndrome score after nonoperative management for locally advanced rectal cancer: a potential MRI biomarker - Thomas, Rehema J.; Derasari, Shrey; Palmquist, Sarah M.; Samms, Nichole; Andring, Lauren; Holliday, Emma B. (Frontiers in Oncology, 2026)
BackgroundNonoperative management is increasingly offered to patients who achieve a complete clinical response to neoadjuvant therapy for rectal cancer. However, long-term bowel dysfunction and fecal incontinence can occur, potentially due in part to post-radiation fibrosis and atrophy of the pelvic floor muscles. In this pilot study, we investigated post-radiation changes in the levator ani muscles and their association with long-term patient-reported bowel dysfunction and incontinence scores.MethodsFifteen patients with rectal cancer treated with definitive chemoradiation followed by non-operative management were included. 2D and volumetric measurements of the levator ani were made on pre-treatment and 1-year post-radiation MRI. The changes in levator ani width and volume were correlated with the Low Anterior Resection Syndrome (LARS) and Fecal Incontinence Quality of Life (FiQOL) scores at least 1-year post treatment.ResultsThe 2D and volumetric measurements of the levator ani decreased between pre-treatment and 1-year post-radiation. (-21.0% and –21.7%, respectively; both P<0.01). The decrease in 2D levator ani measurements was positively associated with LARS score (Pearson r(13) = 0.55; P = .03) but not FiQOL score. The decrease in volumetric levator ani measurements was not significantly correlated with LARS or FiQOL scores.ConclusionsDecrease in 2D measurements of the levator ani from pre-treatment to 1-year post-radiation is correlated with higher LARS scores, indicating worse bowel function, perhaps due to radiation fibrosis and atrophy. This imaging biomarker may help to identify patients who could most benefit from pelvic floor physical therapy interventions. Further studies with larger cohorts are required to validate these findings.